Gait adaptations on a treadmill in the moderate exercise intensity domain – Comparison between older adults with and without a history of falls - Kyra Woitzik; Arber Gashi; Tania Zieschang; Jessica Koschate-Storm (PLoS ONE, 2026)
Objective Older adults face the major risk of falls, potentially resulting in severe functional impairment or death. Many fall scenarios involve components of walking, which is the most common activity in daily life. This study investigated gait adaptations in older adults with and without a history of falls during moderate exercise intensities on a treadmill. The aim was to determine if differences in gait parameters, particularly step length (SL), become more pronounced throughout an interval at moderate exercise intensity, and whether such differences might reflect gait adaptions associated with an elevated fall risk. Methods A total of 87 participants were included, of whom 44 had experienced a fall event within the past 12 months or a severe fall within the past five years that resulted in hospitalization or a fracture. Spatiotemporal gait parameters were recorded on a treadmill during preferred walking speed (PWS), 50% PWS, and at different intervals of a six-minute walking trial at the first ventilatory threshold (VT1), resulting in seven distinct intervals that were selected for analysis under successive exercise conditions. Analyses of variance were conducted to compare spatiotemporal gait parameters between the groups (with/without fall history) and across the seven intervals. Results Individuals with a history of falls showed significantly shorter steps across all intervals compared to those without a fall history (p = 0.007), with the most pronounced differences observed during PWS Recovery (PWS following exertion up to VT1; 5.7 cm) and Start VT1 (first of three consecutive phases of a six-minute walking sequence at VT1; 5.3 cm). On average, they also took wider steps (p = 0.083) across all intervals. There was no interaction effect between interval and group for any of the spatiotemporal gait parameters. Conclusion Community-dwelling, physically fit older adults show differences in step length depending on fall history. Differences were most pronounced at the beginning of VT1 exercise (Start VT1) as well as at PWS following VT1 exertion (PWS Recovery). Step length may therefore represent a situational gait characteristic associated with fall history and elevated fall-related concerns, particularly under moderate exercise conditions. Gait adaptions at moderate intensities, especially VT1, may represent relevant targets for preventive interventions aimed at maintaining mobility and safety in older adults.